A numerical study of reducing the concentration of O3 and PM2.5 simultaneously in Taiwan. (15th September 2022) - Chuang, Ming-Tung; Chou, Charles C.-K; Lin, Chuan-Yao; Lee, Ja-Huai; Lin, Wei-Che; Chen, Yi-Ying; Chang, Chih-Chung; Lee, Chung-Te; Kong, Steven Soon-Kai; Lin, Tang-Huang
Abstract: Since the 24-hr PM2.5 (particle aerodynamic diameter less than 2.5 μm) concentration standard was regulated in Taiwan in 2012, the PM2.5 concentration has been decreasing year by year, but the ozone (O3 ) concentration remains almost the same. In particular, the daily maximum 8-hr average O3 (MDA8 O3 ) concentration frequently exceeds the standard. The goal of this study is to find a solution for reducing PM2.5 and O3 simultaneously by numerical modeling. After the Volatile Organic Compounds (VOCS )-limited and nitrogen oxides (NOX )-limited areas were defined in Taiwan, then, in total, 50 scenarios are simulated in this study. In terms of the average in Taiwan, the effect of VOCS emission reduction is better than that of NOX on the decrease in PM2.5 concentration, when the same reduction proportion (20%, 40%) is implemented. While the effect of further NOX emission reduction (60%) will exceed that of VOCS . The decrease in PM2.5 is proportional to the reduction in precursor emissions such as NOX, VOCS, sulfur dioxides (SO2 ), and ammonia (NH3 ). The lower reduction of NOX emission for whole Taiwan caused O3 increases on average but higher reduction can ease the increase, which suggests the implement of NOX emission reductions must be cautious. When comparing administrative jurisdictions in terms of grids, districts/towns, and cities/counties, it was found that controlling NOX and VOCS at a finer spatial resolution of control units did not benefit the decrease in PM2.5 but did benefit the decrease in O3 . The enhanced O3 control strategies obviously cause a higher decrease of O3 throughout Taiwan due to NOX and VOCS emission changes when they are implemented in the right places. Finally, three sets of short-term and long-term goals of controlling PM2.5 and O3 simultaneously are drawn from the comprehensive rankings for all simulated scenarios, depending on whether PM2.5 or O3 control is more urgent. In principle, the short-term scenarios could be ordinary or enhanced version of O3 decrease with lower NOX /VOCS emissions, while the long-term scenario is enhanced version of O3 decrease plus high emission reductions for all precursors. Graphical abstract: Image 1 Highlights: Strategies including NOX emission reduction all over Taiwan is not recommended. NOX /VOCS reduction exerted on NOX /VOCS -limited regimes is strongly suggested. High NOx reduction is more effective than VOCS reduction on decrease of PM2.5 . Enhanced O3 control strategies cause a higher decrease of O3 throughout Taiwan. Decrease for PM2.5 is proportional to reduction of precursor emissions, not for O3 .